THE BUSINESS PLATFORM FOR EXCHANGE OF THE IDEAS, EXPERIENCE AND TECHNOLOGIES (FOLLOWING THE RESULTS OF THE 24TH INTERNATIONAL SCIENTIFIC AND TECHNICAL CONFERENCE «FOUNDRY PRODUCTION AND METALLURGY 2016. BELARUS» AND INFORMATION EXHIBITION OF FOUNDRY PRODUCTION AND METALLURGICAL TECHNOLOGIES) - Yu. N. Fasevich (Литьë и металлургия, 2017)
.